Epithelial-Myoepithelial Carcinoma of Salivary Glands. Issue 1 (January 2015) - Turk, Andrew T.
<x xml:space="preserve">Abstract</x> Abstract Primary clear cell tumors of the salivary glands include epithelial-myoepithelial carcinoma, clear cell carcinoma, and clear cell myoepithelial carcinoma. Epithelial-myoepithelial carcinoma comprises intercalated duct-like structures with an inner component of epithelial cells, surrounded by an outer component of clear myoepithelial cells. Clear cell carcinoma consists exclusively of luminal-type epithelial cells, whereas myoepithelial carcinoma shows only cells that demonstrate myoepithelial differentiation. Clear cell predominance within myoepithelial carcinoma is rare but well described. Despite several commonalities between these entities, various features distinguish them from one another. Epithelial-myoepithelial carcinoma and clear cell carcinoma are more common among female patients, whereas clear cell myoepithelial carcinoma occurs equally frequently in men and women. Epithelial-myoepithelial carcinoma and clear cell myoepithelial carcinoma characteristically affect the parotid gland and show multinodular expansive growth, whereas clear cell carcinoma usually arises in minor salivary glands and invades as smaller cellular nests. Molecular studies have identified chromosomal rearrangements involving EWSR1 (most frequently creating EWSR1-ATF1 fusion) in approximately 80% of clear cell carcinoma cases. The distinctive characteristics of these lesions are important to understand and consider, given the substantial morphologic and clinical overlap between them. The similarities and differences among these 3 entities constitute the focus of this review.